A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 8 PEKANBARU IN TRANSFORMING ACTIVE INTO PASSIVE SENTENCES AND VICE VERSA - Damila, Dinda; Gultom, Effendy; ', H. Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This descriptive research is aimed at finding out the ability of the second year students of SMAN 8 Pekanbaru in transforming Active into Passive Sentences and Vice Versa. The research data were collected in January 2017. The subject of this research were class XI IPA 5 and XI IPA 6 consists of 68 students. The data were obtained from a test to the students in the form essay. The results administrated of the research showed that the second year students’ ability at SMAN 8 Pekanbaru in the transforming of active into passive sentences got the mean score of 62.3, and in transforming passive into active sentences got the mean score of 59.9.Keywords: Students’ ability, Transforming, Active sentences, Passive sentences